Body Heat: Temperature and Life on Earth - Blumberg, Mark Samuel (Harvard University Press, 2004)
Whether you're a polar bear giving birth to cubs in an Arctic winter, a camel going days without water in the desert heat, or merely a suburbanite without air conditioning in a heat wave, your comfort and even survival depend on how well you adapt to extreme temperatures. In this entertaining and illuminating book, biopsychologist Mark Blumberg explores the many ways that temperature rules the lives of all animals (including us). He moves from the physical principles that govern the flow of heat in and out of our bodies to the many complex evolutionary devices animals use to exploit those principles for their own benefit. In the process Blumberg tells wonderful stories of evolutionary and scientific ingenuity--how penguins withstand Antarctic winters by huddling together by the thousands, how vulnerable embryos of many species are to extremes of temperature during their development, why people survive hour-long drowning accidents in winter but not in summer, how certain plants generate heat (the skunk cabbage enough to melt snow around it). We also hear of systems gone awry--how desert species given too much water can drink themselves into bloated immobility, why anorexics often complain of feeling cold, and why you can't sleep if the room is too hot or too cold. After reading this book, you'll never look at a thermostat in quite the same way again.